HUMAN TRAFFICKING IN INDONESIA, THE DIALECTIC OF POVERTY AND CORRUPTION - Ariadne, Evie; Pratamawaty, Benazir Bona; Limilia, Putri (Sosiohumaniora, 2021)
After thirteen years of Law Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons implemented, it still unable to release Indonesia from cases of trafficking in persons. Indonesia, is not only as primarily a source country in the trafficking process, but it is also used as a destination and transit country. And which is very terrible, all provinces (34 provinces) in Indonesia are the origin and destination of trafficking in persons and the victims are mostly experienced by women and children. The most common forms of trafficking are for forced labour and sexual exploitation as women, children and men are moved domestically and across international borders. They are exploited in the sectors of the fishing and fish processing industry, construction; plantation, oil palm plantation, mining and manufacturing. The poverty factor is considered to be the main trigger for prospective Indonesian workers. Another thing is because of natural disasters which are also vulnerable to human trafficking. In addition, endemic corruption among government officials contributes to the vulnerability of trafficking in persons, especially in the travel, hotel and labour recruitment industries. The phenomenon of globalization is one of the factors in the spread of contemporary (modern) issues, which affected to human trafficking. Advances information technology, are opportunities for the expansion of crime networks, both national and transnational (across borders). The borderless world maks cross-cultural social integration, people move around freely without any obstacles, causes various modes of crime to emerge, such as human trafficking.